Reciprocal effects of stable and temporary components of neuroticism and affective disorders: results of a longitudinal cohort study. Issue 2 (January 2014) - Spinhoven, P.; Penelo, E.; de Rooij, M.; Penninx, B. W.; Ormel, J.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Cross-sectional studies show that neuroticism is strongly associated with affective disorders. We investigated whether neuroticism and affective disorders mutually reinforce each other over time, setting off a potential downward spiral. Method A total of 2981 adults aged 18–65 years, consisting of healthy controls, persons with a prior history of affective disorders and persons with a current affective disorder were assessed at baseline (T1) and 2 (T2) and 4 years (T3) later. At each wave, affective disorders according to DSM-IV criteria were assessed with the Composite Interview Diagnostic Instrument (CIDI) version 2.1 and neuroticism with the Neuroticism–Extraversion–Openness Five Factor Inventory (NEO-FFI). Results Using structural equation models the association of distress disorders (i.e. dysthymia, depressive disorder, generalized anxiety disorder) and fear disorders (i.e. social anxiety disorder, panic disorder, agoraphobia without panic) with neuroticism could be attributed to three components: (a) a strong correlation of the stable components of distress and fear disorders with the stable trait component of neuroticism; (b) a modest contemporaneous association of change in distress and fear disorders with change in neuroticism; (c) a small to modest delayed effect of change in distress and fear disorders on change in neuroticism. Moreover, neuroticism scores in participants newly affected at T2 but remitted at T3 did not differ from their pre-morbid scores at T1. Conclusions Our results do not support a positive feedback cycle of changes in psychopathology and changes in neuroticism. In the context of a relative stability of neuroticism and affective disorders, only modest contemporaneous and small to modest delayed effects of psychopathology on neuroticism were observed.